Peran Minat Beli dalam Memediasi Pengaruh Price dan Product Quality terhadap Keputusan Pembelian Pada Konsumen Kedai Kopi Lingkar Malang - Fahrul Ulum (Fakultas Ekonomi dan Bisnis Islam, 2024)
Coffee shops have become one of the popular gathering places in society. The coffee industry in Indonesia is experiencing rapid growth. This growth has encouraged more and more coffee shops to appear, both small and large scale. With so many coffee shops starting to appear, competition is also getting tougher. This research aims to test and analyze the role of purchase intention in mediating the influence of price and product quality on purchasing decisions among consumers of the Malang Lingkar Coffee shop. Lingkar Malang Coffee Shop is one of the coffee shops in the city of Malang. This shop not only provides a coffee menu, but there are several other menus that provide many choices of beverage products so that consumers can choose products that suit their wishes. The research data used is primary data, which was obtained through distributing questionnaires to the sample. The sample in this study consisted of 80 respondents. The type of research carried out in this research is research explanatory reseach with a quantitative approach. The data collection instrument used in this research was a questionnaire. The data analysis method used in this research is Partial Least Square (PLS). The results obtained from this research conclude that the price variable does not influence the purchase intention and purchasing decisions of consumers at the Lingkar Malang Coffee shop. Then product quality and purchasing intention influence purchasing decisions. Product quality also influences purchase intention. Furthermore, the price variable in the research does not influence purchasing decisions among consumers of the Kopi Lingkar Malang shop which is mediated by purchase intention. Then, product quality in this research influences consumer purchasing decisions which are mediated by purchase intention. Keywords: Purchase Intention; Price; Product Quality; Purchasing Decision